2008
DOI: 10.1007/s11999-008-0121-y
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surgical Approach on Outcome in Birmingham Hip Resurfacing

Abstract: Level III, therapeutic study. See the Guidelines for authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 22 publications
2
32
0
2
Order By: Relevance
“…The clinical results in terms of ROM, hip scores, and activity levels compared well with those reported by others [15,16,24,31,32,38,39]. Radiographically, sclerotic changes around the short femoral stem (pedestal sign) were detected in 40% of the hips, which is less than the 60% reported by Pollard et al [32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The clinical results in terms of ROM, hip scores, and activity levels compared well with those reported by others [15,16,24,31,32,38,39]. Radiographically, sclerotic changes around the short femoral stem (pedestal sign) were detected in 40% of the hips, which is less than the 60% reported by Pollard et al [32].…”
Section: Discussionsupporting
confidence: 82%
“…Unfortunately, we cannot draw valid conclusions in comparison with other HRA implants as our series focused only on the Durom prosthesis. However, better outcomes in terms of failure or revision have been reported for the BHR; 4-to 7-year survival rates varied between 94% and 100% [15,16,24,31,32,38,39]. The data from the Australian Joint Registry also suggested that the BHR has the lowest 5-year revision rate of all devices compared [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear if the length of the incision improves the functional outcome. Surgical approach has not affected outcome of hip resurfacing [33]. Aggressive rehabilitation and not incision length apparently shortens recovery [48].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, even if Myers et al [23] and McBryde et al [24] suggest that the surgical approach slightly modifies the position of the femoral implant and survival, it is vital for the surgeon to preserve the vascularity of the femoral head and neck [25].…”
Section: Discussionmentioning
confidence: 99%